Penyelesaian Tindak Pidana Pencucian Uang - Roy Saputra (CV. Rayyan Dwi Bharata, 2025)
Criminal acts of money laundering is a criminal offense or derivative crime is always preceded by the predicate offense, because the object of the crime of money laundering is the proceeds of predicate offenses. This has implications for the formulation of money laundering in Article 3, 4 and 5 of Law No. 8 of 2010 Concerning the Prevention and Combating of Money Laundering. Where each article contained elements of criminal acts of money laundering and treasure in the wash proceeds of predicate offenses. So it is not possible in case of money laundering stand alone without preceded by the predicate offense. In terms of substantive criminal law, the element of